Interpretation of 4000 performed sperm assays, comparison with assisted reproduction results - Trávník, Pavel; Veselá, Kateřina; Oráčová, Eva; Tauwinklová, Gabriela; Veselý, Jan; Hromadová, Lenka (Abstracts of the 3rd Czech and International Congress of Andrology, 2008)
In our clinic we performed in the period 1999-2008 more than 4000 sperm assays. Obtained values were analysed and they were compared with related IVF/ICSI cycles outcome. The 1738 related IVF/ICSI cycles were used for the assisted reproduction outcome analysis, in 1395 of them was treated by ICSI alone, 215 by IVF alone, and 128 with both methods. Material and methods: In concordance with WHO criteria, the volume, concentration, motility, morphology (using strict criteria in stained smears), total sperm count, total progressive motile sperm count, and total count of sperm with normal morphology were evaluated. They were parsed in the aspect of age, the cross correlation of above mentioned criteria, and the IVF and ICSI outcome (fertilization rate, embryo in vitro development, pregnancy rate, abortion rate). Results: Sperm assays of 3345 men were carried out. The mean age was 32.6 years (16.9 to 76.9 years), the sperm concentration 68.0 millions per ml (0 to 560 millions per ml), motility A 26.5% (0 to 93%), motility B 27.6% (0 to 93%), normal morphology 20.9% (0 to 100%). The 3% of men were azoospermic and 0.75% cryptozoospermic. The concentration, motility, and sperm morphology was age dependent with some maxima and minima, with the apparent decline in the group from 56 to 77 years old men. The fertilization rate, in vitro development, pregnancy rate and abortion rate were found to partially correlate with the sperm parameters. Conclusions: We found that the distribution of sperm values is rather logarithmic than normal, and set of examined men probably creates several independent subsets. The average sperm concentration, motility, and morphology exceed in our file the WHO criteria. The assisted reproduction outcome correlates only partially with the sperm parameters.